2015
DOI: 10.1136/bmjopen-2015-008415
|View full text |Cite
|
Sign up to set email alerts
|

The mental health of US Black women: the roles of social context and severe intimate partner violence

Abstract: ObjectiveBlack women continue to have rates of mental health conditions that can be negative for their well-being. This study examined the contribution of social and contextual factors and severe physical intimate partner violence on the mental health of US Black women (African-American and Caribbean Black).SettingData were largely collected via in-person community interviews at participants’ homes.ParticipantsWe studied 3277 African-American and Black Caribbean women from the 2001–2003 National Survey of Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 43 publications
2
42
0
1
Order By: Relevance
“…In this context, vulnerabilities related to the use of substances can be enhanced by the existence of racial prejudice, judgment and violence. It is evident that the highest rates of violence are generally observed among married black women, which highlights gender and race inequality as a factor that increases vulnerability (12) .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, vulnerabilities related to the use of substances can be enhanced by the existence of racial prejudice, judgment and violence. It is evident that the highest rates of violence are generally observed among married black women, which highlights gender and race inequality as a factor that increases vulnerability (12) .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, there is no accurate information on the prevalence of STIs in the young black population, due to the importance that a health service gives to ethnic and racial aspects, as these data can favor the development of most effective for each group public policies. 19 A study in the United States showed that women with partners who had already been arrested or incarcerated had a higher prevalence and chance of contracting sexually transmitted infections. 20 The findings reinforced the importance of programs that seek to reduce male HIV-risk behaviors and to promote care DISCUSSION https://periodicos.ufpe.br/revistas/revistaenfermagem/index engagement after release from imprisonment, highlighting the need for programs for testing and treating sexually communicable infections to incarcerated men or women or with incarcerated partners.…”
Section: Class 6: the Role Of The State In Combating Ethnic-racial VImentioning
confidence: 99%
“…In 2016, almost half of the 1.6 million Black immigrants in the U.S. came from the Caribbean countries of Jamaica and Haiti [ 11 ]. Caribbean Blacks and African-Americans have different cultural and historical colonial experiences that may portend different patterns as protective or predictive of mental health disorders [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For mood disorders, in addition to confirming the sometimes lower prevalence of MDD for African American versus White women [ 20 , 21 , 22 , 23 ], studies from the NSAL found no differences in the prevalence of MDD or dysthymia for African American and Caribbean Black women [ 12 , 22 ]; African American mothers had elevated rates of bipolar disorder [ 23 ]. When nativity was considered, U.S.-born Caribbean women were found to have higher rates of any mood disorder compared to foreign-born Caribbean women [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation